Ecotourism social media initiatives in China - Cheng, Mingming; Wong, I.; Wearing, S.; McDonald, M. (Routledge, 2017)
The purpose of this study is to investigate the use of social media by ecotourism management agencies and how this potentially changes the relationship between the ecotourist and the natural environment. It examines the meaning of ecotourism and the way that social media shapes visitor perceptions and meaning through an examination of the content of 775 Sina microblog postings from five leading ecotourism site management agencies in China. In order to gain a deeper understanding of the social media postings, a series of semi-structured interviews was also conducted with followers and management agencies. The findings provide an enhanced understanding of ecotourism marketing and its impacts on the ecotourist while also creating a framework for the use of social media to market ecotourism. The framework outlines the importance of the meanings associated with this form of communication through its promotional appeal to tourists and the outcomes for both the ecotourist and site management.